The Effect of Demonstration Method on Students’ Speaking Skill - Febriyadi, Radhika Putri; Apud, Apud; Anita, Anita (English Education: Jurnal Tadris Bahasa Inggris, 2024)
The aim of this study is to assess the impact of the demonstration method on students' speaking skills. The research addresses the following questions: what is the baseline proficiency level of students' speaking skills prior to implementing the demonstthe ration method? How does the application of the demonstration method influence the speaking skills of class X students at SMKN 6 Kota Serang? And what is the overall effect of the the demonstration method on students' speaking abilities? An an experimental methodology was employed, involving 57 students divided into two groups: X Akuntansi (experimental) and X TKJ (control). Data were gathered through pre-test and post-tests assessments, with subsequent analysis conducted using the t-test. The significance level was set at 5%, corresponding to a critical value (tt) of 1.67. The calculated t-value (to) yielded a result of 7.13, indicating that to > tt. Therefore, the alternative hypothesis (Ha) was supported, suggesting a substantial effect of the demonstration method on enhancing students’ speaking skills at SMKN 6 Kota Serang